2018
DOI: 10.1111/joes.12292
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Know About the Impact of Intellectual Property Rights on the Foreign Direct Investment Location (Country) Choice? A Review and Research Agenda

Abstract: Despite a longstanding debate, at both a theoretical and empirical level, research on the relationship between foreign direct investment (FDI) and intellectual property rights (IPRs) remains scant and ambiguous. As a result, the link between IPR strength and multinational enterprises' (MNEs) propensity to invest is unproven and seemingly dependent on a number of factors. We critically review the theory and evidence of the influence of IPRs on FDI and MNEs' investment location (country) decisions both to 'take … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…More broadly, our study also relates to the abundant literature on the determinants of FDI (e.g., Brada et al., 2021; Erdogan, 2014; Faeth, 2009; Noon et al., 2018). …”
mentioning
confidence: 74%
See 1 more Smart Citation
“…More broadly, our study also relates to the abundant literature on the determinants of FDI (e.g., Brada et al., 2021; Erdogan, 2014; Faeth, 2009; Noon et al., 2018). …”
mentioning
confidence: 74%
“…3 This is consistent with the fact that many firms lost their political connections after numerous officials were prosecuted in this campaign against corruption; thus, we are able to verify the underlying rationale by employing the subsample after 2013. 4 More broadly, our study also relates to the abundant literature on the determinants of FDI (e.g., Brada et al, 2021;Erdogan, 2014;Faeth, 2009;Noon et al, 2018). 5 These alternative institutions often evolve to deal with contacting or financial issues, such as repeated interactions, culture, networks, and so forth (e.g., Araujo et al, 2016;Chaney, 2014).…”
Section: N O T E Smentioning
confidence: 88%
“…Against this backcloth, and despite several decades of research on the IPR-FDI nexus, the relationship between the two remains ambiguous. As pointedly noted by the recent review article by Noon, De Vita and Appleyard (2019), conflicting theoretical predictions on how the strength of a country's IPR system can affect MNCs' FDI location choice have been hypothesized over the years and, taken collectively, the empirical literature is equally contradictory and inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Second, scarcity of quality FDI data has led to systematic inconsistencies in measurement across most previous studies, often plaguing the reliability of reported results (Noon et al, 2019). In particular, aggregate FDI measures based on count data or the net accumulated stock of FDI provide insufficiently precise measures to gauge how FDI responds to changes in IPRs over time, especially when short sample periods -which in many papers are restricted to one, two or three years (see, e.g., Ferrantino, 1993;Mansfield, 1995;Braga and Fink, 1998;Maskus, 2000;Nunnenkamp and Spatz, 2004;Seyoum, 2006;Nicholson, 2007;Watkins and Taylor, 2010) -are considered.…”
Section: Introductionmentioning
confidence: 99%
“…Among important F.D.I.-related issues, intellectual property rights (I.P.R.) protections have attracted decades of studies (Kukharskyy, 2020;Maskus, 1998Maskus, , 2015Noon et al, 2019). From an ex ante perspective, I.P.R.…”
Section: Introductionmentioning
confidence: 99%